Contract Hydrographic Surveys - Haslam, D. W. (The International Hydrographic Review, 2015)
National hydrographers — with responsibility for surveying to the accuracy needed for navigational safety — have been under pressure to keep pace with the rapidly increased draught of tankers, operating along new routes to new ports and offshore terminals, and accepting reduced underkeel clearances, at a time when offshore hydrocarbon and other new marine resource activities have called for extensive data collection, interpretation and presentation of quite different sets of parameters. The paper describes how contract surveys have been used to increase the surveying carried out for the safety of navigation in British waters.